2005
DOI: 10.2113/176.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic evidence for Cimmerian events in NW Caucasus (Russia)

Abstract: The Upper Permian and Triassic sequences of the NW Caucasus present a good record of the Cimmerian events, rather undisturbed by the subsequent Alpine deformations. Original field work with new fossil identifications, microfacies analysis, and sandstone petrography were carried out. During the late Permian, active strike-slip basins were filled by continental clastics successions. Marine ingressions during the latest Permian, led to the formation of sponge reefs and skeletal carbonate ramps. During the Triassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Unfortunately, detailed paleotectonic reconstructions have not been attempted for this region yet, and therefore, it is difficult to justify an exact paleoposition for the Western Caucasus. However, we agree with the suggestion of Gaetani et al (2005), who suggested strike-slip movements in this region. They might have been related to the activity of the major shear zone located just to the north of the Western Caucasus (Arthaud and Matte, 1977;Ruban and Yoshioka, 2005;Tawadros et al, 2006).…”
Section: Western Caucasussupporting
confidence: 92%
See 4 more Smart Citations
“…Unfortunately, detailed paleotectonic reconstructions have not been attempted for this region yet, and therefore, it is difficult to justify an exact paleoposition for the Western Caucasus. However, we agree with the suggestion of Gaetani et al (2005), who suggested strike-slip movements in this region. They might have been related to the activity of the major shear zone located just to the north of the Western Caucasus (Arthaud and Matte, 1977;Ruban and Yoshioka, 2005;Tawadros et al, 2006).…”
Section: Western Caucasussupporting
confidence: 92%
“…They are the Khodzinskaja Group (Norian-Lower Rhaetian), embracing carbonates, including reefal limestones (packstones in the lower part, overlain by wackestones in the upper part), and the Khadzhokhskaja Group (Upper Norian), encompassing shales with sandstone and carbonate interbeds. Rostovtsev et al (1979) established a Norian age for the clastic deposits in the Kamennomostskij area with the typical Monotis assemblage; however, this age was not confirmed by the studies of Gaetani et al (2005). In this paper, we prefer to continue the usage of the Khadzhokhskaja Group following the lithostratigraphic framework of Rostovtsev et al (1979) because of their macrofaunal evidence and our field observations.…”
Section: Western Caucasusmentioning
confidence: 78%
See 3 more Smart Citations